The SLAPTAG: A new molecular tag adapted for the development of a high-performance, low-cost, affinity chromatography system - Muruaga, Emanuel Javier (2022)
The SLAPTAG is a novel molecular TAG derived from a protein domain present in the sequence of Lactobacillus acidophilus SlpA (SlpA284-444). Proteins from different biological sources, with different molecular weights or biochemical functions, can be fused in frame to the SLAPTAG and efficiently purified by the specific binding to a bacterial-derived chromatographic matrix named here Bio-Matrix (BM). To set an optimized protocol for the SLAPTAG-based affinity chromatography (SAC) different binding and elution conditions were evaluated. The binding equilibrium between SLAPTAG and BM was reached after a few minutes at 4°C, being the apparent dissociation constant (KD) of 4.3 uM, a value similar to the one determined for other S-layer proteins and their respective bacterial cell-walls. A reporter protein was generated (H6-GFP-SLAPTAG) to compare the efficiency of SAC against a commercial system based on a Ni2+-charged agarose matrix, observing no differences in the H6-GFP-SLAPTAG purification performance. The stability and reusability of the BM were evaluated, and it was determined that the matrix was stable for more than a year, being possible to reuse it five times without a significant loss in the efficiency for protein purification. Alternatively, we explored the recovery of bound SLAP-tagged proteins by proteolysis using the SLAPASE (a SLAP-tagged version of the HRV-3c protease) that released a tag-less GFP (SLAPTAG-less). Additionally, iron nanoparticles were linked to the BM and the resulting BMmag was successfully adapted for a magnetic SAC, a technique that can be potentially applied for high-throughput-out protein production and purification.